1996
DOI: 10.1128/aac.40.3.755
|View full text |Cite
|
Sign up to set email alerts
|

Use of standardized SCID-hu Thy/Liv mouse model for preclinical efficacy testing of anti-human immunodeficiency virus type 1 compounds

Abstract: We have developed standardized procedures and practices for infection of SCID-hu Thy/Liv mice with human immunodeficiency virus type 1 for the prophylactic administration of antiviral compounds and for evaluation of the antiviral effect in vivo. Endpoint analyses included quantitation of viral load by intracellular p24 enzyme-linked immunosorbent assay, DNA PCR for the presence of proviral genomes, flow cytometry to measure the representation of CD4 ؉ and CD8 ؉ cells, and cocultivation for the isolation of vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 27 publications
6
60
0
2
Order By: Relevance
“…Unfortunately, the NVP concentrations more than 3 h post-dosing were lower than the limit of quantification by HPLC assay. Therefore, the AUC 0-3 was applied to evaluate the interaction between RFP and NVP in this study, although the plasma NVP concentration in the present study is consistent with those observed in SCID mice in a previous report (Rabin et al 1996).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Unfortunately, the NVP concentrations more than 3 h post-dosing were lower than the limit of quantification by HPLC assay. Therefore, the AUC 0-3 was applied to evaluate the interaction between RFP and NVP in this study, although the plasma NVP concentration in the present study is consistent with those observed in SCID mice in a previous report (Rabin et al 1996).…”
Section: Discussionsupporting
confidence: 85%
“…On day 5, blood was collected by cardiac puncture under diethyl ether (Wako Pure Chemicals Ltd., Osaka, Japan) anaesthesia at 0.5, 1.5 and 3 h after dosing (4-5 mice per time-point). Plasma of each blood sample was separated by centrifugation at 3500 rpm for 15 min at 4 C and then kept at À30 C. The plasma samples were determined by validated reversed-phase high performance liquid chromatography with ultraviolet detector (JASCO Corp., Tokyo, Japan) using a modified method reported by Rabin et al (1996). The chromatographic separation was achieved with a CrestPak C18T-5 column (C 18 , 250 mm  4.6 mm; 5 mm).…”
Section: In Vivo Drug Interaction Studymentioning
confidence: 99%
“…41 The efficacy of bevirimat was evaluated in vivo using the SCID-hu Thy/Liv mouse model, a well accepted animal model for testing HIV drugs. 53,54 Twicedaily oral administration of bevirimat to HIV-1-infected SCID-hu Thy/Liv mice reduced implant viral loads in a dose-dependent manner, causing reductions of 42 log 10 in HIV-1 RNA and Z 90% both in implant p24 concentration and in percentage of Gag-p24 1 thymocytes at 100 mg/kg per day, while preserving immature and mature T-cell populations. 55 Antiviral activity was observed in the mice at plasma concentrations that are achievable in humans by oral dosing.…”
Section: Preclinical Studies Of Bevirimatmentioning
confidence: 98%
“…The in vitro activity results for DSB have been extended by the demonstration of efficacy in vivo using the severe combined immunodeficiency (SCID)-hu Thy/Liv mouse model, a well-accepted animal model for testing HIV drugs [51,52]. Treatment of HIV-1 implant-infected mice with an orally bioavailable salt form of DSB by twice-daily oral gavage reduced the level of implant-associated virus in a dosedependent manner, causing reductions of ≥ 90% in p24 levels and in Gag-p24 + thymocytes at 30 and 100 mg/kg/day as well as protection of thymocytes from virus-mediated depletion [53].…”
Section: In Vitro and In Vivo Studies Of 3-o-(3′3′-dimethylsuccinyl)mentioning
confidence: 99%